Two new species of Lysianassidae Dana, 1849 from Australia: Riwo zeidleri and Socarnella delectabilis (Crustacea: Peracarida: Amphipoda) - Hughes, L. E.; Lowry, J. K. (Zootaxa, 2015)
The new species Riwo zeidleri and Socarnella delectabilis are described. Prior to this study Riwo Lowry & Stoddart, 1995 was a monotypic genus, while Socarnella Walker, 1904 consisted of only two described species. The distribution of Riwo is expanded southwards from northern Papua New Guinea and the Great Barrier Reef to the south coast of Australia and the distribution of Socarnella is expanded further southward from Sri Lanka and the South China Sea, to the west coast of Australia.